2021
DOI: 10.1590/1807-3107bor-2021.vol35.0137
|View full text |Cite
|
Sign up to set email alerts
|

Effect of xylitol varnishes on enamel remineralization of immature teeth: in vitro and in situ studies

Abstract: We evaluated the efficacy of xylitol varnishes on the remineralization of newly erupted permanent and deciduous teeth in vitro and in situ. Human enamel specimens were randomly allocated to 8 groups (n = 15/group). Artificial caries lesions were produced and enamel alterations were quantified by surface/subsurface hardness and transverse microradiography. The blocks were then treated with the following varnishes: Duraphat TM ; 20 wt% xylitol (146 μm) varnish; 20 wt% milled xylitol (80 μm) varnish, and placebo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…Within the cyclical pH model, remineralization is an important process, which is why in this study it was carried out with a remineralizing solution at a pH of 7.0 in which the samples were immersed for 21 hours after the application of the remineralizing agents, treated for a period of 15 days; On the other hand, some authors (SahitiJ Sai., 2020;Pinto Priscila., 2017;Santos Gabriela., 2021) carry out the remineralization process using artificial saliva, changing it every 24 hours before immersion of the treated samples for 7 days only; Likewise, Rodríguez (Rodriguez Maria Ana, 2018) used human saliva as a remineralizing medium, collecting daily fresh saliva from five volunteers, after which the different saliva samples were mixed and shaken to obtain a homogeneous solution. However, this process is not completely reliable since the oral conditions of each volunteer are different, which is why in this study a remineralizing solution was prepared instead.…”
Section: Discussionmentioning
confidence: 99%
“…Within the cyclical pH model, remineralization is an important process, which is why in this study it was carried out with a remineralizing solution at a pH of 7.0 in which the samples were immersed for 21 hours after the application of the remineralizing agents, treated for a period of 15 days; On the other hand, some authors (SahitiJ Sai., 2020;Pinto Priscila., 2017;Santos Gabriela., 2021) carry out the remineralization process using artificial saliva, changing it every 24 hours before immersion of the treated samples for 7 days only; Likewise, Rodríguez (Rodriguez Maria Ana, 2018) used human saliva as a remineralizing medium, collecting daily fresh saliva from five volunteers, after which the different saliva samples were mixed and shaken to obtain a homogeneous solution. However, this process is not completely reliable since the oral conditions of each volunteer are different, which is why in this study a remineralizing solution was prepared instead.…”
Section: Discussionmentioning
confidence: 99%
“…However, the manufacturer does not report the concentration of xylitol added to the varnish. Since the best results of previous studies were obtained with 20% xylitol in varnishes (16,17,18,19) or 10% xylitol in toothpaste (20), it is not possible to say whether the effect of xylitol added to Profluorid™ is only favoring the taste of the varnish or if it could also be therapeutic.…”
Section: Inhibition Of Incipient Caries Lesion Progression By Differe...mentioning
confidence: 99%
“…The increased levels of calcium and phosphate in stimulated saliva limit demineralization and enhance remineralization. 16 In an in vitro study, Siqueira et al 17 found that a varnish containing xylitol had a significantly higher remineralization capacity compared to non-xylitol varnishes. 18…”
Section: Sugar Alcohols Xylitolmentioning
confidence: 99%